(untitled) (International Journal of Engineering Sciences & Management Research, 2014)
The study presents a performance evaluation of 2G (GSM/EDGE) and 3G (UMTS/HSPA) cellular networks in India based on key performance indicators (KPIs) such as throughput, latency, call drop rate, and signal strength. Using data collected from five major telecom circles Delhi, Mumbai, Kolkata, Chennai, and Lucknow this paper compares average network performance parameters. Results show that 3G networks outperform 2G in data throughput (average 2G: 120 kbps; 3G: 3.1 Mbps), latency (2G: 500 ms; 3G: 120 ms), and user satisfaction (2G: 72%; 3G: 89%). However, 2G remains crucial for rural connectivity due to its broader coverage. The study concludes that while 3G networks represent a substantial improvement in data-centric performance, 2G continues to play a vital role in low-data-demand areas.